1985
DOI: 10.2105/ajph.75.9.1071
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of swimming-related illness. II. Morbidity and the microbiological quality of water.

Abstract: A prospective cohort epidemiological-microbiological study was carried out at 10 beaches in Ontario, Canada. Lake water and sediment samples collected at the beaches were analyzed for fecal coliforms, fecal streptococci, heterotrophic bacteria, Pseudomonas aeruginosa, and total staphylococci. Mean fecal coliform levels in the surface water of the lakes were within accepted guidelines. Bacterial densities were found to be approximately 10 times higher

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 12 publications
1
48
0
Order By: Relevance
“…In the Hong Kong study, E. coli was also a reasonable indicator, but there was a relatively low correlation between total symptom rates and enterococci or faecal streptococci. In the Canadian study (Seyfried et al 1985a(Seyfried et al , 1985b, the Cabelli protocol was followed at freshwater bathing sites in Ontario. Although there were significant statistical relationships between disease incidence and both faecal coliforms and faecal streptococci, total staphylococci were the best indicator of disease risk.…”
Section: Alternatives To Faecal Streptococcimentioning
confidence: 99%
See 1 more Smart Citation
“…In the Hong Kong study, E. coli was also a reasonable indicator, but there was a relatively low correlation between total symptom rates and enterococci or faecal streptococci. In the Canadian study (Seyfried et al 1985a(Seyfried et al , 1985b, the Cabelli protocol was followed at freshwater bathing sites in Ontario. Although there were significant statistical relationships between disease incidence and both faecal coliforms and faecal streptococci, total staphylococci were the best indicator of disease risk.…”
Section: Alternatives To Faecal Streptococcimentioning
confidence: 99%
“…For example, a large-scale study conducted at Hong Kong Beaches (Cheung et al 1988) showed that the best enteric infection predictor was E. coli. Others have shown health risk to be best indicated by staphylococci (e.g., Seyfried et al 1985aSeyfried et al , 1985bCalderon et al 1991), although levels of these bacteria may also be related to bather density in semi-enclosed waters. However, in the studies by Seyfried et al (1985a;1985b) faecal streptococci were counted, rather than enterococci.…”
Section: Recently a Document Entitied Provisional Microbiological Wamentioning
confidence: 99%
“…The combination of several indicators is likely to offer a global picture of water quality (23). The ndings of this study suggest that fecal coliforms represent the most sensitive bacterial indicator when it comes to seasonal uctuation related to increased human presence during the summer months.…”
Section: Discussionmentioning
confidence: 81%
“…They accept the guide values of the investigated bacteria up to 500 cfu/100 ml of marine water for coliform bacteria and 100 cfu/100 ml for both E. coli and faecal streptococci. The combination of the three indicators is likely to offer a global picture of water quality (19).…”
Section: Resultsmentioning
confidence: 99%